2012
DOI: 10.1111/j.1365-2559.2012.04277.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of osteopontin and LMX1A expression with World Health Organization grade in meningiomas and gliomas

Abstract: Higher immunostaining intensity for OPN and LMX1A correlated with WHO grades for meningiomas and some gliomas. Contrary to our expectations, LMX1A staining in WHO grade IV gliomas was shown to be weaker than in WHO grade III tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Since six distinct somatic mutations in the LMX1A gene were previously reported in gliomas (COSMIC database; cancer.sanger.ac.uk [94]), potential postnatal functions of LMX1A can be suspected. Evidence also supports a correlation between LMX1A immunostaining intensity and the grading system of primary brain tumors in meningiomas and some gliomas (see [95] and Section 4.2 for details). In mDA neurons, the expression of Lmx1a in postmitotic neurons diminishes with aging, but significant levels remain present in the adult brain [81,91,96].…”
Section: Lmx1a and Lmx1b Maintain Neuronal Homeostasis In The Adult Bmentioning
confidence: 69%
See 1 more Smart Citation
“…Since six distinct somatic mutations in the LMX1A gene were previously reported in gliomas (COSMIC database; cancer.sanger.ac.uk [94]), potential postnatal functions of LMX1A can be suspected. Evidence also supports a correlation between LMX1A immunostaining intensity and the grading system of primary brain tumors in meningiomas and some gliomas (see [95] and Section 4.2 for details). In mDA neurons, the expression of Lmx1a in postmitotic neurons diminishes with aging, but significant levels remain present in the adult brain [81,91,96].…”
Section: Lmx1a and Lmx1b Maintain Neuronal Homeostasis In The Adult Bmentioning
confidence: 69%
“…A growing body of evidence has shown that LMX1A plays an important role in cancer. Briefly, immunohistological analysis of brain tumors has shown that the LMX1A protein level correlates with grades of meningiomas and some gliomas, except for grade IV gliomas in which Lmx1a staining is weaker than grade III [95]. The LMX1A expression level can also predict the grade and aggressiveness of ovarian [120] and pancreatic cancers [121].…”
Section: Role Of In Human Cancersmentioning
confidence: 99%
“…Meanwhile, OPN as a multifunctional protein has also been involved in every single step of cancer progression including cancer cell adhesion, tumor invasion, metastasis and angiogenesis [68]. Moreover, OPN was overexpressed in different solid tumors, including, but not limited to breast cancer [9], non-small cell lung cancer [10], colorectal cancer [11], hepatocellular carcinoma [12] and glioma [13]. Accumulated studies [1423] also measured the OPN expression in primary tumor tissues or plasma in GC patients and investigated the clinical relevance between OPN and survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many studies have shown that the abnormal expression of OPN is closely related to the occurrence and development of liver cancer, colon cancer and some gynecological malignancies. The mechanism may be that OPN promotes the formation of new blood vessels, chemotactic transfer of cytokines, adhesion and extracellular matrix, while inhibiting apoptosis in varying degrees [20].…”
Section: Discussionmentioning
confidence: 99%